Rancang Bangun Sistem Monitoring Kebocoran Gas, Suhu, dan Kelembapan pada Dapur Berbasis Internet of Things Menggunakan Mikrokontroler Wemos D1 Mini - Ganis Sanhaji; Irdi Pratama Putra; Ishak Abdul Rojak (Dinasti Research, 2023)
This research is about the design of a gas leak monitoring system, temperature, and humidity in an Internet of Things (IoT) based kitchen using a Wemos D1 Mini microcontroller. The system aims to overcome the problem of uncontrolled temperature and humidity that affect the quality of food, as well as the high risk of LPG gas explosion due to leakage. A gas leak monitoring system using MQ2 sensor, monitoring temperature and humidity values using DHT 11 sensor and microcontroller using Wemos D1 Mini. The MQ2 sensor will detect a gas leak from the volume of gas in the room. If the gas value in the room is 300 ppm, the buzzer will sound. The DHT 11 sensor will monitor the temperature and humidity percentage. Then the Wemos d1 mini will send the value to the BLYNK database and will be displayed in the application using Kodular. This research is expected to contribute to the field of IoT-based monitoring systems, improving the safety and comfort of the kitchen environment.